Generational difference of refractive error in the baseline study of the Beijing Myopia Progression Study. Issue 6 (16th April 2013) - Liang, Yuan Bo; Lin, Zhong; Vasudevan, Balamurali; Jhanji, Vishal; Young, Alvin; Gao, Tie Ying; Rong, Shi Song; Wang, Ning Li; Ciuffreda, Kenneth J
Abstract : Aims: To report the refractive error difference (RED) between parents and their children and the estimated single generational myopic shift in an urban area in China. Methods: 395 children aged 6–17 years and their parents, who had been enrolled in the Beijing Myopia Progression Study were included. Cycloplegic and non-cycloplegic refraction of the children and parents were performed, respectively. RED was defined as the difference between the average parental spherical equivalent (SE) and the average SE of their children. Binomial fitted curves of RED were plotted as a function of the children's age. Generational myopic shift was defined as the estimated RED according to the prediction model at the age of 18 years. Results: 395 families were enrolled. The RED was positively correlated with the children's age (rspearman =0.58, p<0.001). The RED (median (25th and 75th percentile)) was −1.88 (−3.23 to −1.00) dioptres (D) in children at 6.0–7.9 years of age, and it increased to 1.53 (−0.12 to 3.44) D in children at 16.0–17.9 years of age. The SE of the children approached the average SE of their parents at the age of 11 years. At the age of 18 years, the children's estimated myopic shift would be 1.94 D. Conclusions: In this sample, children's refractive errors at the age of 11 years were already similar to their parents. Moreover, the estimated myopia in children at the age of 18 years would be up to 2.0 D higher than their parents. This remarkable single-generation myopic shift indicates that there are likely effects of environmental factors on myopia development in urban Chinese children.